The politics of gender and women's agency in post-colonial Sri Lanka - Thiruchandran, Selvy (Colombo : Women's Education and Research Centre, 1997)
On women participation in postcolonial Sri Lankan politics post-1978; a study.
Keywords: Women -- Political activity -- Sri Lanka; Postcolonialism -- Sri Lanka; Sri Lanka -- Politics and government -- 1978-